The Role of NLRP3 Inflammasome in Pneumococcal Infections - Surabhi, Surabhi; Cuypers, Fabian; Hammerschmidt, Sven; Siemens, Nikolai (Frontiers in Immunology, 2020)
Inflammasomes are innate immune sensors that regulate caspase-1 mediated inflammation in response to environmental, host- and pathogen-derived factors. The NLRP3 inflammasome is highly versatile as it is activated by a diverse range of stimuli. However, excessive or chronic inflammasome activation and subsequent interleukin-1β (IL-1β) release are implicated in the pathogenesis of various autoimmune diseases such as rheumatoid arthritis, inflammatory bowel disease, and diabetes. Accordingly, inflammasome inhibitor therapy has a therapeutic benefit in these diseases. In contrast, NLRP3 inflammasome is an important defense mechanism against microbial infections. IL-1β antagonizes bacterial invasion and dissemination. Unfortunately, patients receiving IL-1β or inflammasome inhibitors are reported to be at a disproportionate risk to experience invasive bacterial infections including pneumococcal infections. Pneumococci are typical colonizers of immunocompromised individuals and a leading cause of community-acquired pneumonia worldwide. Here, we summarize the current limited knowledge of inflammasome activation in pneumococcal infections of the respiratory tract and how inflammasome inhibition may benefit these infections in immunocompromised patients.